2015
DOI: 10.1186/s12885-015-1595-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of O6 methylguanine-DNA-methyl transferase in prolactinomas: a correlative study of promoter methylation and pathological features in 136 cases

Abstract: BackgroundLow-level expression of O6 methylguanine-DNA-methyl transferase (MGMT) prolactinomas has been noted previously in case reports, although what modulates MGMT expression remains unclear. This study therefore aimed to delineate the factors regulating MGMT expression in prolactinomas.MethodsWe retrospectively reviewed 136 prolactinoma patients who were treated in our center between January 2000 and September 2013. Expression of MGMT, Ki-67, and p53 protein were examined by immunohistochemical staining, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Preliminary data proposed that DNA repair enzyme O6methylguanine DNA methyltransferase (MGMT) expression was correlated with the clinical benefit of TMZ in APT and PC patients (35). According to our previous research, the majority of prolactinomas showed minimal MGMT expression, which provide a rational for the utility of TMZ to manage the aggressive prolactinomas (36). MGMT may attenuate the effect of TMZ by removing additional alkyl groups.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Preliminary data proposed that DNA repair enzyme O6methylguanine DNA methyltransferase (MGMT) expression was correlated with the clinical benefit of TMZ in APT and PC patients (35). According to our previous research, the majority of prolactinomas showed minimal MGMT expression, which provide a rational for the utility of TMZ to manage the aggressive prolactinomas (36). MGMT may attenuate the effect of TMZ by removing additional alkyl groups.…”
Section: Discussionmentioning
confidence: 96%
“…In our study, patients with methylated MGMT promoter generate a higher radiological response, but the difference is not as significant as the effect of MGMT expression. It implies that MGMT expression level is not only affiliated with the promoter methylation status but also regulated by other unique epigenetic and transcriptional microenvironment factors (28,29,36). Moreover, the MGMT promoter methylation is simply classified as the positive group and the negative group without a cutoff of grading as definite as the gene expression, which might be the principal event for the reduction of correlation between MGMT promoter methylation and TMZ response (20).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported low MGMT expression in 26% of functional PA in a cohort of adult-dominated patients [24]. Low MGMT expression was also reported in prolactinoma (78-85.71%) [36,37], corticotroph adenomas (62.5-81.48%) [37,38], and somatotroph adenomas (90.0-91.7%) [37,39]. In the current study, the functional PAs were 32/38 (84.21%), of which 13/32 (34.21%) showed low MGMT expression.…”
Section: Discussionmentioning
confidence: 76%
“…In glioblastoma (GBM), low expression of MGMT as determined by immunohistochemistry has been associated with responsiveness to temozolomide; 16 however, only MGMT promoter methylation, which results in silencing of the MGMT gene, has been validated as a predictive and prognostic marker. 17 In pituitary adenomas, an inverse relationship between MGMT promoter methylation and MGMT expression has been reported by some, 18,19 but not all, investigators. 20,21 At this time, the evidence primarily supports a relationship between treatment response and low MGMT expression by immunohistochemistry as opposed to MGMT promoter methylation, which is technically more reliable.…”
Section: Chemotherapy In the Treatment Of Pituitary Adenomasmentioning
confidence: 93%